Global Characteristics and Trends in Research on Ferroptosis: A Data-Driven Bibliometric Study. (17th January 2022) - Dong, Xueting; Tan, Yaochong; Zhuang, Donglin; Hu, Tingting; Zhao, Mingyi
Abstract : Ferroptosis, an iron-dependent form of regulated cell death, has drawn an increasing amount of attention since it was first mentioned in 2012 and is found to play a significant role in the treatment of certain diseases. Our study is aimed at analysing the scientific output of ferroptosis research and at driving future research into novel publications. Publications focused on ferroptosis were retrieved from the SCI-EXPANDED database of the Web of Science Core Collection and were screened according to inclusion criteria. CiteSpace V and Microsoft Excel 2016 were used to evaluate and visualize the results, including generating network maps and analysing annual publications, country, category, references and cocited references, and keywords. As of October 1, 2021, a total of 1690 original articles related to ferroptosis were included, and the overall trend of the number of publications rapidly increased. Among the common categories in the field of ferroptosis, the most common category was biochemistry and molecular biology. Worldwide, China and the United States were the leading countries for research production. The retrieved 1690 publications received 44, 650 citations, with an average of 26.42 citations per paper (October 1, 2021). By citation analysis, Scott J Dixon's article in 2012 was the most symbolic reference and the earliest publication in the field of ferroptosis, with the highest citation rate (2709 times). Among the most common keywords, most were related to the mechanisms and regulatory networks of ferroptosis. Furthermore, with accumulating evidence demonstrating the role of ferroptosis in cancers and other diseases, inducing ferroptosis in clinical treatment is becoming a new research focus that should be closely monitored.